2017
DOI: 10.1002/2016wr019641
|View full text |Cite
|
Sign up to set email alerts
|

Improved water balance component estimates through joint assimilation of GRACE water storage and SMOS soil moisture retrievals

Abstract: The accuracy of global water balance estimates is limited by the lack of observations at large scale and the uncertainties of model simulations. Global retrievals of terrestrial water storage (TWS) change and soil moisture (SM) from satellites provide an opportunity to improve model estimates through data assimilation. However, combining these two data sets is challenging due to the disparity in temporal and spatial resolution at both vertical and horizontal scale. For the first time, TWS observations from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
125
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(145 citation statements)
references
References 63 publications
12
125
0
Order By: Relevance
“…In addition, it is challenging to improve surface soil moisture varying rapidly in time, using a monthly mean GRACE observation. Tian et al (2017) utilized the satellite soil moisture observation from Soil Moisture and Ocean Salinity (SMOS, Kerr et al, 2001) in addition to GRACE data for their data assimilation and showed a clear improvement in the top soil moisture estimate. The GC approach with complementary observations at higher temporal resolution should be considered, particularly to enhance the surface soil moisture computation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it is challenging to improve surface soil moisture varying rapidly in time, using a monthly mean GRACE observation. Tian et al (2017) utilized the satellite soil moisture observation from Soil Moisture and Ocean Salinity (SMOS, Kerr et al, 2001) in addition to GRACE data for their data assimilation and showed a clear improvement in the top soil moisture estimate. The GC approach with complementary observations at higher temporal resolution should be considered, particularly to enhance the surface soil moisture computation.…”
Section: Resultsmentioning
confidence: 99%
“…Australia experiences significant climate variability; for example, the Millennium Drought starting from late 1990 (Van Dijk et al, 2013) and extremely wet conditions during several La Niña episodes (Trenberth, 2012;Han, 2017). These periods are referred as "Big Dry" and "Big Wet" (Ummenhofer et al, 2011;Xie et al, 2016).…”
Section: Assessment Of Mass Variation In the Past 13 Yearsmentioning
confidence: 99%
See 2 more Smart Citations
“…As an integrative measure of vertical changes in total water storage, the results of GRACE trend analyses have been validated by multi-source data such as finer satellite observations, modelling data, and lots of in-situ data [74][75][76][77][78][79][80][81][82][83][84][85][86][87]. The BJD region is characterized as having a typical arid or hyper arid climate, with the annual potential evaporation exceeding over four times that of the amount of annual precipitation [88].…”
Section: Tws Decline Despite the Stable Precipitationmentioning
confidence: 99%